Mitigasi Risiko Hukum dalam Penyelesaian Sengketa Kontrak Konstruksi melalui Dewan Sengketa - Shantyabudi, Helda; Azheri, Busyra; Mulyati, Nani (Faculty of Law, Andalas University, 2023)
Construction projects are considered a sector loaded with risks. Almost every construction service industry activity always appears as a claim, often becoming a dispute. The legal basis for the settlement of construction contract disputes is regulated in Article 88 of Law Number 2 of 2017 by directing dispute settlement through an out-of-court mechanism and providing support for the existence of a dispute board to avoid claims before they arise into disputes. However, Law Number 2 of 2017 does not provide detailed regulations regarding dispute boards, so parties in Indonesia's construction service industry doubt its effectiveness. The research aim is to analyze the implementation of legal risk mitigation to avoid construction contract disputes. The research methodology is done in normative legal research by combining historical, statute, comparative, and conceptual approaches. Research data sources are secondary legal materials and research data collection methods conducted by library research. The results of the study show that there are fundamental differences between construction claims and lawsuits. The concept of dispute avoidance is designed to change the culture to enable proactive dispute prevention and real-time dispute resolution. The dispute board rules in Indonesia are regulated in the Regulation of Minister of Public Works and Public Housing Number 11 of 2021. The output of the dispute boards is a formal decision that is final and binding. In this case, it is not equivalent to an enforceable decision but is contractually binding.